Pharmaceutical therapy programme for remodeling heart prevention after Q-wave myocardial infarction - R. M. Gafurova; A. A. Abdullaev; Z. A. Umakhanova; U. A. Islamova (Российский кардиологический журнал, 2007)
In 445 patients after Q-wave myocardial infarction, Q-IM (mean age 54,3 years; 433 men, 12 women), echocardiography parameters of left ventricular (LV) remodeling were examined after the discharge, 6 and 12 months later. Sphericity index, systolic myocardial stress and relative heart wall thickness parameters were calculated. All patients were randomized into three intervention groups: Group I (n=87) received standard therapy (metoprolol, aspirin, statins, other medications if necessary); plus enalapril and trimetazidine; Group II (n=105) - trimetazidine; Group III (n=108) - enalapril. Control group (n=145), receiving standard therapy only, was matched by gender, age, and myocardial damage type. Six months later, echocardiography LV remodeling parameters improved in all three intervention groups (especially in trimetazidine plus enalapril group), remaining unchanged in the control group. One year later, LV remodeling parameters did not differ significantly from the baseline ones.